2018
DOI: 10.1002/aenm.201800029
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable All‐Polymer Solar Cells with High Tolerance on Blend Ratios

Abstract: comprised of a conjugated polymer as the electron donor and a fullerene derivative as the electron acceptor. [2,3] Conventional fullerene acceptors like [6,6]-phenyl-C61 butyric acid methyl ester (PCBM) may be unfavorable for practical application, due to the inefficient absorption in visible and near-infrared (IR) regions, fixed molecular structure, complex purification process, and other complications well-documented in the literature. [4][5][6][7][8] In addition, the morphology of polymer-fullerene blends i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
178
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(190 citation statements)
references
References 55 publications
9
178
1
Order By: Relevance
“…Furthermore, most fullerene or small molecular based acceptors suffer from an initial PCE loss of up to 30–40 % (“burn‐in loss”) in times as short as several hundred hours with (Figures a,b). Thus, PBDB‐T:ITIC suffers significant aging and thermal degradation in a short time while those fabricated with 10:1 PBDB‐T:N2200 exhibit remarkable aging and thermal stability . The devices were stored on a hot plate at 80 °C in a glovebox without encapsulation between measurements to investigate the thermal stability.…”
Section: Advantages Of Apscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most fullerene or small molecular based acceptors suffer from an initial PCE loss of up to 30–40 % (“burn‐in loss”) in times as short as several hundred hours with (Figures a,b). Thus, PBDB‐T:ITIC suffers significant aging and thermal degradation in a short time while those fabricated with 10:1 PBDB‐T:N2200 exhibit remarkable aging and thermal stability . The devices were stored on a hot plate at 80 °C in a glovebox without encapsulation between measurements to investigate the thermal stability.…”
Section: Advantages Of Apscsmentioning
confidence: 99%
“…Thus, Ma et al. showed that the PCEs of PBDB‐T:P(NDI2OD‐T2) cells vary far less than those based on PBDB‐T:ITIC blends (Figure c) . They fabricated and compared the performance of non‐fullerene PSCs based on PBDB‐T :acceptor blends at various weight blend ratios, from 1:10 to 20:1.…”
Section: Advantages Of Apscsmentioning
confidence: 99%
“…Nonfullerene molecular or polymeric electron acceptors offer unique opportunities for photovoltaic applications due to their flexible structural tunability and new device features that emerge at the donor/acceptor heterojunction. In addition, the adoption of nonfullerene materials can offer exceptional stability which has not been achieved in previous polymer–fullerene systems . This progression demonstrates the potential for nonfullerene PSCs and its advantages for further design opportunities for efficient and stable solar cells for large‐scale applications.…”
Section: Introductionmentioning
confidence: 95%
“…Conjugated molecules and polymers tend to exhibit better thermal stability than conventional fullerene derivatives. This property presents unique potential as these materials are less prone to thermal stress and exhibit better phase stability . However, the morphology of bulk heterojunction (BHJ) blend film is detrimental to charge transport and recombination.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the XPS results of Figure S9, Supporting Information, the surface chemical compositions of both the PEDOT:PSS and SM5 films exhibit almost negligible changes after thermal annealing at 85 °C for 50 h in ambient air conditions. Therefore, the similarly observed ambient‐air thermal instabilities from PEDOT:PSS‐ and SM5‐based devices are likely to originate from the thermal degradation of the PBDB‐T:ITIC photoactive layer during the initial test period before the HTL films begin to have any noticeable effect on device stability . Ambient air stability of PBDB‐T:ITIC‐based devices without encapsulation at room temperature was also investigated, as shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%